1987
DOI: 10.1029/jc092ic08p08183
|View full text |Cite
|
Sign up to set email alerts
|

The influence of warm‐core rings on slope water entering the Gulf of Maine

Abstract: The seasonal baroclinic circulation in the Gulf of Maine is partly determined by the distribution of dense water that enters from the continental slope and spreads over sills into the deep basins of the Gulf. The slope water enters the Gulf as an intermittent deep flow through the Northeast Channel, which provides the principal connection with the Atlantic Ocean. Warm‐core rings from the Gulf Stream occasionally approach the mouth of the Northeast Channel, and at times, ring water contributes to or modifies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 22 publications
1
44
0
Order By: Relevance
“…Data from stations identified by the filled circles are shown in Figure 9; the station names are from a 1982 survey, partly a result of the intense tidal stirring, which continually brings deep nutrients into the euphotic zone, In summer satellite images, the tidally mixed water from the eastern gulf is evident in a plume of cold surface water extending southwestward along the coast from Grand Manan Island to the vicinity of Mt. Desert Island (Fig, I), The cold water traces a nontidal coastal current that is associated with the contrast between buoyant nearshore water and deeper, more saline water confined in Jordan Basin (Brooks, 1985). A fraction of the coastal current turns offshore east of Penobscot Bay and enters a cyclonic gyre that develops in Jordan Basin in the summer.…”
Section: Introductionmentioning
confidence: 95%
“…Data from stations identified by the filled circles are shown in Figure 9; the station names are from a 1982 survey, partly a result of the intense tidal stirring, which continually brings deep nutrients into the euphotic zone, In summer satellite images, the tidally mixed water from the eastern gulf is evident in a plume of cold surface water extending southwestward along the coast from Grand Manan Island to the vicinity of Mt. Desert Island (Fig, I), The cold water traces a nontidal coastal current that is associated with the contrast between buoyant nearshore water and deeper, more saline water confined in Jordan Basin (Brooks, 1985). A fraction of the coastal current turns offshore east of Penobscot Bay and enters a cyclonic gyre that develops in Jordan Basin in the summer.…”
Section: Introductionmentioning
confidence: 95%
“…Brooks & Townsend (1989) have observed that the coastal current along the coastal Gulf of Maine, which is presumed to transport larvae away from the eastern Maine spawning ground ), is extremely variable, being subject to redirection as a function of the amount of dense slope water residing immediately offshore in Jordan Basin. The amount of that slope water which enters the Gulf of Maine is in turn likely influenced by the presence of warm core Gulf Stream rings at the mouth of the Northeast Channel (Townsend & Spinrad 1986, Brooks 1987, and hence is an unpredictable and variable phenomen. It is not inconceivable that episodes of greater offshore transport of larvae, at least from the eastern Gulf of Maine, result in better survival through the winter.…”
Section: Recruitment Implicationsmentioning
confidence: 99%
“…Nutrients within this basin are upwelled and entrained in the strong south-west flow of the Eastern Maine coastal current (Townsend et al, 1987;Brooks and Townsend, 1989). Part of this current may recirculate in one or more large counter-clockwise gyres centered over Jordan and Wilkinson Basins (Bigelow, 1927;Brooks, 1985Brooks, , 1987Butman and Beardsley, 1987). Some of the central waters may exit the Gulf either via a narrow subsurface jet hugging the north side of Georges Bank or by recirculating around Georges Bank and returning to the New England Shelf south of Cape Cod.…”
Section: Introductionmentioning
confidence: 99%